The Role of Instructional Models in Improving Students’ Mastery of Science Concepts: A Literature Review - Sintya Dewi Lestari; Paramita Putri Apriyani; Ni Ketut Anggriani; Dewa Dwi Pranahita (Indonesian Journal of Applied Science and Technology, 2026)
Science concept mastery is an important aspect of learning because it plays a crucial role in enhancing students’ ability to understand and apply scientific knowledge. However, in practice, science concept mastery remains a common challenge due to the dominance of conventional, teacher-centered instructional approaches. This study aims to examine various learning models used to improve students’ science concept mastery, identify the most dominant learning model, and analyze the distribution of research based on educational level, science subject matter, and the dependent variables investigated. The research employed a literature review method involving 16 national and international journal articles published between 2016 and 2025, analyzed using the PRISMA approach. The findings indicate that guided inquiry is the most widely implemented learning model and demonstrates consistent effectiveness, particularly in physics and integrated science learning at the senior high school level. In addition, Problem-Based Learning (PBL) and Project-Based Learning (PjBL) serve as effective supporting models in connecting science concepts to real-life contexts and fostering higher-order thinking skills. These findings emphasize the importance of implementing inquiry-oriented and student-centered learning models to enhance students’ mastery of science concepts.